Heart rate variability during orthostatic test, and central hemodynamic parameters in coronary heart disease patients with arterial hypertension - A. D. Ibatov (Российский кардиологический журнал)
Autonomic regulation and central hemodynamics in patients with coronary heart disease and arterial hypertension were examined. In 107 individuals with CHD, various cardiovascular tests were performed; heart rate variability, central hemodynamic parameters were assessed, with integral rheography in rest and during orthostatic test. All participants were divided into two groups, by presence/absence of arterial hypertension. Comparing to normotensive CHD patients, participants with CHD and hypertension had reduced heart rate variability and elevated initial specific peripheral resistance. Orthostatic test reaction was presented by significant decrease in parasympathic and moderate decrease in sympathic activity, with moderately lowered systolic blood pressure, and mildly raised specific peripheral resistance. These features of autonomic regulation and hemodinamics during orthostatic test in CHD patients with arterial hypertension may affect duration of anginal episode, and angina progression towards myocardial infarction. After test improvement of heart rate variability, comparing to basic levels, is an evidence of controlled physical exercise positive effect on adaptation mechanisms and functional status in patients with CHD, regardless of their blood pressure levels. This is another argument supporting high importance of moderate physical training in rehabilitation of such patients.